Identification of endothelin-converting enzyme-2 as an autoantigen in autoimmune polyendocrine syndrome type 1. (19th May 2017) - Smith-Anttila, Casey J. A.; Bensing, Sophie; Alimohammadi, Mohammad; Dalin, Frida; Oscarson, Mikael; Zhang, Ming-Dong; Perheentupa, Jaakko; Husebye, Eystein S.; Gustafsson, Jan; Björklund, Peyman; Fransson, Anette; Nordmark, Gunnel; et al.
Abstract: Autoimmune polyendocrine syndrome type 1 (APS1) is a rare monogenic autoimmune disorder caused by mutations in the autoimmune regulator (AIRE) gene. High titer autoantibodies are a characteristic feature of APS1 and are often associated with particular disease manifestations. Pituitary deficits are reported in up to 7% of all APS1 patients, with immunoreactivity to pituitary tissue frequently reported. We aimed to isolate and identify specific pituitary autoantigens in patients with APS1. Immunoscreening of a pituitary cDNA expression library identified endothelin-converting enzyme (ECE)-2 as a potential candidate autoantigen. Immunoreactivity against ECE-2 was detected in 46% APS1 patient sera, with no immunoreactivity detectable in patients with other autoimmune disorders or healthy controls. Quantitative-PCR showed ECE-2 mRNA to be most abundantly expressed in the pancreas with high levels also in the pituitary and brain. In the pancreas ECE-2 was co-expressed with insulin or somatostatin, but not glucagon and was widely expressed in GH producing cells in the guinea pig pituitary. The correlation between immunoreactivity against ECE-2 and the major recognized clinical phenotypes of APS1 including hypopituitarism was not apparent. Our results identify ECE-2 as a specific autoantigen in APS1 with a restricted neuroendocrine distribution.